(untitled) (Applied Biological Research, 2024)
Cordyceps militaris produces one of the most important bioactive compound cordycepin. It is quite challenging to synthesize the substantial quantities of this compound for industrial use. The present study was aimed to optimize some cultural conditions of C. militaris for maximum mycelial growth, fruiting body formation and cordycepin production. In this study, C. militaris DMR 1164 was subjected to serial dilution and 500 µL mycelium was plated onto the potato dextrose agar (PDA) plates and incubated at 22°C for 7 days in dark to isolate single cell colonies. Randomly purified single cell mycelial colony of C. militaris was subjected to optimization studies to improve its growth potential. The study revealed the optimal temperature and pH for C. militaris mycelial growth to be 20⁰C and pH 6. The modified PDA medium No. IV was found ideal medium for achieving luxuriant mycelial growth as compared to other five test media. Liquid medium was suitable for quick mycelial growth than solid medium; whereas, brown rice based solid medium was optimal for fruiting body formation when incubated under light/dark alternate cycles for 65 days. The amount of cordycepin, determined spectrophotometrically at 460 nm, was 8.1 + 1.32 mg g-1 fruiting body. The large scale production of cordycepin can possibly be achieved by exploiting the above studied conditions.